PEMBUATAN DAN UJI KUALITAS BIODIESEL DARI MINYAK JELANTAH - Syamsidar HS (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2013)
Research of this experiment aim to know how quality and exploiting of biodiesel yielded of Used Cooking oils. Oil Sample used Cooking oils taken away from by merchant fry roadside. This research early from purification of ex- cooking oil /used cooking oils. Pure oil result of purification is later, then used for the making of biodiesel with method reaction of transesterifikation covering some phase that is warm-up and mixing, dissociation and precipitation, netralisasi, draining and wash and also omission of water. Yielded Biodiesel of oil used cooking oils is hereinafter tested by its quality to know do biodiesel of oil of used cooking oils this competent to be used upon which burn alternative or do not. As for test of is quality of which is done/conducted that is determination specific gravity, viskositas, water rate, sour number, free gliserol, total gliserol, ester rate of alkil number and of iod. Result of research indicate that pursuant to test of is quality of which have been done/conducted by hence biodiesel of oil of jelantah can be used as by alternative fuel substitution of diesel fuel because have fulfilled standard of biodiesel Indonesia.